2020
DOI: 10.1108/bpmj-04-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

An ERP success model based on agency theory and IS success model

Abstract: PurposeThe purpose of this paper is to propose an enterprise resource planning (ERP) implementation model based on the agency theory and the Delone and McLean information systems (IS) success model. This paper answers two major research questions: (i) how does client–consultant interaction affect the outcome of ERP implementation projects; and (ii) how can this interaction be managed effectively to ensure successful project outcomes?Design/methodology/approachAn electronic banking institution in Africa was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…For the last 20 years, enterprise resource planning (ERP) have been the cornerstone of centralized business process control in organizations (Kamdjoug et al , 2019). While these programs have proved to be essential to business process productivity and, as a result, business growth, successful adoption of ERPs remains a major challenge for many modern companies.…”
Section: Theoretical Literature and Hypothesis Developmentmentioning
confidence: 99%
“…For the last 20 years, enterprise resource planning (ERP) have been the cornerstone of centralized business process control in organizations (Kamdjoug et al , 2019). While these programs have proved to be essential to business process productivity and, as a result, business growth, successful adoption of ERPs remains a major challenge for many modern companies.…”
Section: Theoretical Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Mayeh et al (2016) stated that ERP's adoption requires the sharing of data from internal and external organisations; this data exchange process requires mutual trust. Kamdjoug et al (2020) explained that there is a sense of concern if one of the parties in the supply chain misuses the data and exploits the others' interests. Also, the asymmetry of interests poses a challenge to ERP's adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Because of increasing ERP implementation failures and varying ERP benefits, many studies have reported on Critical Success Factors (CSFs) influencing ERP success (Ram et al, 2013). These factors were meant to assist managers in planning and executing ERP systems successfully (Kamdjoug et al, 2020). Some CSF classifications are across the ERP lifecycle (Anaya, 2013), whereas some CSF classifications are based on the specific ERP implementation phase (Staehr et al, 2012).…”
Section: Critical Success Factorsmentioning
confidence: 99%